Enabling Voice: Perceptions of Schooling from Rural Aboriginal Youth at Risk of Entering the Juvenile Justice System - Edwards-Groves, Christine; Murray, With Colleen (The Australian Journal of Indigenous Education, 2008)
Abstract In this article the perceptions of school experiences by male Aboriginal youth at risk of becoming in contact with the juvenile justice system are presented. These adolescent boys, from inland rural New South Wales, attend Tirkandi Inaburra Cultural and Development Centre (Tirkandi). Tirkandi is a short term residential centre designed to provide at risk boys with an opportunity to participate in strengths-based culturally appropriate educational, cultural, social and personal programs. In this study, participants give detailed accounts of schooling describing their lives as students. Their voices offer a powerful insight into the situated construction of agency and identity in classroom life, culture and learning among Aboriginal students. They serve as a window in to how perceptions and voice are socially-culturally-politically configured – both in their production and deployment. Further, they show the complexity and deeply problematic nature of how individuals' lived experiences collide across contexts when these contexts operate in isolation. The insider's voices, presented in this paper, are significant because they offer valuable insights that will encourage educators to be challenged by the relational architecturesdominating teaching practices. These voices form not just the backdrop but the centerpiece for discussion in this paper.